Pengaruh periode pra-kondisi dan penutupan sungkup terhadap daya hidup planlet karet (Hevea brasiliensis Muell. Arg) Effect of pre-condition period and vessel closure on the survival rate of rubber (Hevea brasiliensis Muell. Arg) plantlets - Masna Maya SINTA; . NURHAIMI-HARIS; . SUMARYONO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2013)
Acclimatization of plantlets is a critical stage in the micropropagation of many plants. An experiment was conducted to determine the effect of pre-condition period and vessel closure on the growth and survival rate of rubber (Hevea brasiliensis Muell.Arg.) plantlets derived from in vitro microcutting during acclimatization. Plantlets were planted in plastic pots containing mixed growing media after being conditioned in ex vitro environment for 0, 3 and 6 days. Five closure vessel treatments were closed pots placed in opened container, opened pots in closed glass container, closed pots in closed glass container, opened pots in closed plastic container, and closed pots in closed plastic container. Observation on leaf conditions, rooting frequency, and plant height were conducted at 1.5 months and on the percentage of survive plantlets at 1.5 and 3 months after acclimatization. The results showed that pre-condition was required to increase survival rate and growth of the plantlets. Pre-condition period of six days gave a higher survival rate than 0 and 3 days which reached 100% and 93% on opened pot in closed plastic container and closed pot in opened container, respectively after 1.5 months and was reduced to 80% after three months of acclimatization. The highest formation of new leaves and roots were also obtained on six days pre-condition period. Plantlets with pre-condition for six days and were planted on closed pots in an opened container had the best rooting frequency which was 90%. The result showed that the highest survival rate (80%) of rubber plantlets after three months was obtained when the plantlets were pre-conditioned in ex vitro conditions for six days before acclimatization and planted on opened pots in a closed plastic container or closed pots in an opened container.